2017
DOI: 10.1145/3119930
|View full text |Cite
|
Sign up to set email alerts
|

Using Worker Self-Assessments for Competence-Based Pre-Selection in Crowdsourcing Microtasks

Abstract: Paid crowdsourcing platforms have evolved into remarkable marketplaces where requesters can tap into human intelligence to serve a multitude of purposes, and the workforce can benefit through monetary returns for investing their efforts. In this work, we focus on individual crowd worker competencies. By drawing from self-assessment theories in psychology, we show that crowd workers often lack awareness about their true level of competence. Due to this, although workers intend to maintain a high reputation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…• Self-assessment theory (Gadiraju et al, 2016) • Equity Theory (d'Eon et al, 2019) • No analytical lens (n=12)…”
Section: Experiments (20% 14/70)mentioning
confidence: 99%
“…• Self-assessment theory (Gadiraju et al, 2016) • Equity Theory (d'Eon et al, 2019) • No analytical lens (n=12)…”
Section: Experiments (20% 14/70)mentioning
confidence: 99%
“…It is known that assessments by workers are biased. (Gadiraju et al, 2017) showed that crowd workers often lack awareness about their actual level of competence. Incorporating such bias into a self-correction framework would be a challenge for future work.…”
Section: Related Workmentioning
confidence: 99%
“…Workers spend more than 25% of their time searching for tasks that they want to complete [KDM*14]. Thus, in the future, it would be helpful for crowdsourcing platforms to either order the tasks based on their cognitive demands [CIT16] or automatically fetch and suggest tasks to the worker [LRMB15, CIT16, GCB16] based on a self‐assessment report filled in by the worker [GFK*17]. If such a self‐assessment report also includes the results of the ability tests (e.g., colorblindness, visual literacy) that the worker has completed for previous tasks, and these reports are accessible to all experimenters, then experiments could be shorter, more focused on the assessed task, and less cumbersome for the worker.…”
Section: Opportunities and Challengesmentioning
confidence: 99%